Fractionation of heavy metals in sewage sludge and their removal using low-molecular-weight organic acids - Zaleckas, Ernestas; Paulauskas, Valdas; Sendžikienė, Eglė (Journal of Environmental Engineering and Landscape Management, 2013)
The total concentration and the concentrations of individual chemical species of selected heavy metals were estimated in primary and anaerobically digested sewage sludge. The concentration of Zn (1503 mg/kg) was highest and was followed by Cu (201 mg/kg), Cr (196 mg/kg), Pb (56 mg/kg), Ni (44 mg/kg) and Cd (3.6 mg/kg). The metal was divided into 5 fractions (exchangeable (F1), adsorbed (F2), organically bound (F3), bound to carbonates (F4), and residual (F5)) via sequential extraction. The sludge treatment procedure had no significant effect on the fractionation results. In both the primary and anaerobically digested sewage sludge, the heavy metals were ranked according to their mobilities (fractions F1 and F2) in the following order: Ni > Zn > Cu > Cd > Pb > >Cr. Metal stability in the environment was evaluated by the sulphide and residual fraction F5, and the following ranking order was identified: Cr > >Pb≈Ni > Cd > Zn≈Cu. A leaching experiment with low-molecular-weight organic acids (oxalic, acetic and citric acid) revealed that the metal-removal efficiency varied depending on the number of carboxyl groups in the extracting agent, the chemical speciation of the metal (Ni, Zn or Cu) in the sludge and the concentration and pH change of the extracting solution. Acid solutions with a 0.5 M concentration, ranked according to their Zn-removal efficiency, are ranked as follows: citric acid (100%) > acetic acid (78%) > oxalic acid (71%). In all of the cases, citric acid showed the best capacity for the removal of metal from the sludge, with an extraction efficiency ranging from 30–100%, while the Ni and Cu removal efficiencies with the acetic and oxalic acid were less than 40%. First published online: 11 Oct 2012